The influence of simulated worn shoe and foot inversion on heel internal biomechanics during running impact: A subject-specific finite element analysis - Song, Yang; Cen, Xuanzhen; Wang, Meizi; Bálint, Kovács; Tan, Qitao; Sun, Dong; Gao, Shunxiang; Li, Fengping; Gu, Yaodong; Wang, Yan; Zhang, Ming (Journal of biomechanics, 2025)
This study explored how systematic changes in running shoe degradation and foot inversion alter the distribution and peak value of heel pressure and calcaneus stress, as well as the total stress-concentration exposure (TSCE) within the calcaneal bone. A foot-shoe finite element model was employed and three shoe wear conditions (new shoe (CON), moderate worn shoe (MWSC), excessive worn shoe (EWSC)) coupled with three foot inversion angles (0°, 10°, 20°) were further modulated. Simulations were conducted at the impact peak instant during running. Compared to CON0, heel pressure during neutral landings shifted medially and increased with progressive shoe wear, peaking under EWSC0. This shift expanded the high-pressure area by 1.333 cm2 and raised peak pressure by 24.42 %. Foot inversion landings exhibited an opposite trend: increased shoe wear promoted balanced pressure distribution, centralizing the load and eliminating high-pressure areas under EWSC10, where peak pressure was 11.36 % lower than CON10. Calcaneus stress during neutral landings, initially concentrated on the medial calcaneal surface and inferior tuberosity, intensified with wear, expanding high-stress area by 5.276 cm2 and increasing peak stress by 22.79 % under EWSC0. For foot inversion, the high-stress region shifted to the inferior tuberosity, with wear reducing peak stress by 10.41 % and eliminating high-stress area in EWSC10 compared to CON10. TSCE analysis revealed that EWSC10 had the lowest stress exposure (0 %kPa) across all conditions. Worn-out shoes would exacerbate heel internal biomechanics, while these effects may be mitigated by foot inversion, likely due to the formation of a relatively flat and larger contact area between the lateral sole and the ground.